O brincar da criança pré-escolar: estudo de caso em uma escola minicipal de educação infantil - Leal, Leila Leane Lopes (Universidade Federal de São Carlos, 2003)
In this new century early childhood education experiences a magnifying and expansive moment and there appear new researches on this subject which have brought a larger and more adequate comprehension of children and childhood. I emphasize the research about the child s role along history and how the feeling on the childhood has been formed. I remade the way in which the concept of childhood has been built and how this has become a social category by investigating the relationship between playing and being a child. I privileged theoreticians who adopt the historic-cultural perspective, specifically Vygotsky, Leontiev, Elkonin, Mukhina and some Brazilian authors who have promoted recent studies on the subject. Playing is a most important activity of the preschool child as this is the factor which more cooperates to the psychic development in infancy. Considering that the child younger and younger enters into the kindergarten and there remains a greater period of time each day, I analyzed how his or her activities happen in a EMEI (Brazilian City Early childhood education) in S. Carlos, S.P., Brazil. According to parents and teachers communication, I observed that they really play.Considering this, I have made interviews with parents and teachers, as well as some observation sessions in a EMEI. A diference between playing at home and playing at the school was observed to establish the relationships between them and to try recovering the importance of its happening. From these informations there came to me the hypothesis that although the kindergarten teachers know the importance of playing in the EMEI and make it happen, they don t always understand the essentiality of this playing. As they don t generally dominate a sufficient and exact theoretical foundation to allow clarifying some mistaken points towards this infantile activity, teachers don t develop it in a complety way, as a priority in this period of life. I consider that the children s necessities and development can be objects to discussion and reflection in the early childhood education so as to guide the construction of the school projects in a way that their educators (teachers, agents, parents, principals) take part in the process. It s necessary to collectively redefine the methodology to be adopted. But to this it s necessary political will and effective actions in the dimension of public politics. One of these political axes is to invest more in the continued education for the teachers in early childhood education. Another necessary action comprehends the investment on the work conditions.
Keywords: Educação infantil; Professores - formação; Educaçãa e cultura; Brincar; Crianças de 4 a 6 anos; CIENCIAS HUMANAS::EDUCACAO